Does opting in or out affect the take up of incentives in a long running population-based cohort study: A nested randomised trial in ALSPAC - Kate Northstone; Claire Bowring (PLoS ONE, 2025)
Background Financial incentives may be important for improving response rates to data collection activities and for retaining participants in longitudinal studies. However, for large studies, this introduces significant additional costs. We sought to determine whether an opt-in or an opt-out option for receiving financial incentives when completing questionnaires offers any cost saving measures. Methods The Avon Longitudinal Study of Parents and Children has been ongoing for more than 30 years. It has offered a £10 incentive for returning a partly or fully completed annual questionnaire for >10 years, this is provided by default unless a participant chooses to opt out. For questionnaires completed in 2020 by the original parents recruited to the study and by their offspring, we randomised eligible participants to either opt-out or to opt-in to receiving their vouchers. Logistic regressions determined whether opt-out or opt-in made any difference to the proportion of respondents receiving their vouchers. Results Respondents are less likely to choose to receive a thank you for their time in the form of a £10 shopping voucher if they are asked to opt in compared to if they are asked to opt out. The odds ratio, adjusted for baseline characteristics was 3.94 (95% Confidence Interval: 3.49, 4.45). There was no difference in response rates according to whether respondents were randomised to the opt-in or opt-out group. Conclusions ALSPAC now employs an opt-in procedure for respondents receiving their financial incentive when completing a questionnaire. We recommend similar studies that rely on volunteers consider this option if they want to introduce some cost savings without harming overall response rates.